Research on Cultural Integration of Chinese Enterprises’ Overseas Mergers and Acquisitions -Take Haier Group’s acquisition of General Electric as an example - Gaofeng Yu (International Journal of Management and Education in Human Development, 2022)
In recent years, an increasing number of Chinese enterprises are gradually moving towards internationalization through cross-border mergers and acquisitions. However, the process of cross-border mergers and acquisitions is not smooth. Due to improper integration after mergers and acquisitions, especially cultural integration, many Chinese enterprises have failed in cross-border mergers and acquisitions. Taking Haier Group's acquisition of GE's household appliance business as an example, this paper deeply analyzes the differences in national and corporate cultural characteristics of Haier Group's acquisition of GE in different periods, hoping to provide experience and reference value for other multinational enterprises in China to carry out mergers and acquisitions.